Electrical faults detection for the intelligent diagnosis of a photovoltaic generator, March 2014, ISSN/ISBN: 1582-4594 / 1335-3632. - Rezgui Wail; Rezgui Wail; Kadri Ouahab (Journal of Electrical Engineering (JEE), 2014)
In this paper, we proposed a new mathematical model of the I-V characteristic of a faulty photovoltaic generator. It presents its behavior in normal and faulty operations. In particular, when its basic components such as cells, bypass and blocking diodes are subjected to the impedance or reversed polarity faults. The developed model of the faulty PV generator will allow studying of the I-V characteristic, measures the tolerances of the technical functions, avoids numerous experiments, and ensure better assessment of fault consequences.